2011
DOI: 10.2174/138920111798357258
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia: Mechanisms, Current Treatment and Animal Models

Abstract: Fibromyalgia syndrome (FMS) is a chronic pain syndrome characterized by diffuse musculoskeletal pain. In quantitative sensory testing studies, FMS patients display alterations in heat, cold, and mechanical sensitivity. Genetic studies support a key role for the biogenic amine system, and single nucleotide polymorphisms have been identified in serotonin and dopamine transporter and receptor genes of FMS patients. The pathophysiology of fibromyalgia includes contributions from both the ascending and descending s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…31,33,34,41 For example, in people with fibromyalgia, there is enhanced glutamate in the insular cortex and amygdala, [88][89][90] as well as decreased serotonin and increased substance P in the cerebrospinal fluid. 37,91,92 To mimic these chronic, centrally maintained pain conditions, our laboratory developed a model induced by repeated IM acid injections that mimics the symptoms of chronic muscle pain and has enhanced central excitability with sensitization of dorsal horn neurons, increases in glutamate, and phosphorylation of transcription factors and excitatory neurotransmitter receptors. 59,[93][94][95][96] Furthermore, this model of pain is unrelated to tissue damage, has no nerve injury, and is not maintained by continued primary afferent input from the site of injury.…”
Section: Discussionmentioning
confidence: 99%
“…31,33,34,41 For example, in people with fibromyalgia, there is enhanced glutamate in the insular cortex and amygdala, [88][89][90] as well as decreased serotonin and increased substance P in the cerebrospinal fluid. 37,91,92 To mimic these chronic, centrally maintained pain conditions, our laboratory developed a model induced by repeated IM acid injections that mimics the symptoms of chronic muscle pain and has enhanced central excitability with sensitization of dorsal horn neurons, increases in glutamate, and phosphorylation of transcription factors and excitatory neurotransmitter receptors. 59,[93][94][95][96] Furthermore, this model of pain is unrelated to tissue damage, has no nerve injury, and is not maintained by continued primary afferent input from the site of injury.…”
Section: Discussionmentioning
confidence: 99%
“…Fibromyalgia (FM) is a chronic pain syndrome that is characterized by diffuse multifocal pain accompanied by fatigue, sleep disturbances, depression, cognitive, and memory issues, and alterations in sensory processing such as touch, audition, and vision (Wolfe et al, 1990; Brederson et al, 2011). FM patients also have significant limitations in functional mobility, namely difficulties in goal-directed movements due to generalized musculoskeletal pain (e.g., restrictions in tasks such as rising from a chair and walking), which in turn increase their risk of disability (Jones et al, 2010, 2012; Björnsdóttir et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Even though central nervous system (CNS) desensitization is considered the primary mechanism at the root cause of chronic pain in FMS, evidence of the many co-morbid conditions associated with FMS has strongly suggested that other factors, including genetic abnormalities, some involving biogenic amine dysfunction [18], single nucleotide polymorphisms in the serotonin transporter gene, SCL6A4, and dopamine transporter and receptor genes [19,20]. Altered allelic frequencies between FMS patients and controls were also found in the genes encoding γ-aminobutyric acid A receptor β3 (GABRB3), trace amine-associated receptor-1 (TAAR1) and interferon-induced guanylate-binding protein-1 (GBP1) [21].…”
Section: Gene Polymorphisms and Fmsmentioning
confidence: 99%
“…FMS has also been associated with distressful lifestyle [22], hormonal imbalances exemplified by impairment in the hypothalamic/ pituitary/adrenal axis and the growth hormone/insulin-like growth factor-1 paracrine axis [15][16][17][18][19][20][21][22][23], neuroendocrine immunologic dysfunction and defective cell-mediated immunity [24][25][26][27][28][29] all of which may be viewed as contributing to the pathophysiology of FMS.…”
Section: Metabolic Imbalancementioning
confidence: 99%